Assessment of the physiological vulnerability of the endemic and critically endangered Daggernose Shark: A comparative approach to other Carcharhiniformes - Wosnick, Natascha; Chaves, Ana Paula; Dias, Héllida Negrão; Onodera Palmeira Nunes, Ana Rita; Nunes, Jorge Luiz Silva; Hauser-Davis, Rachel Ann (Frontiers in Marine Science, 2023)
Introduction The current Isogomphodon oxyrhynchus (Daggernose Shark) population status Q7points to 99% losses in the last decade due to certain biological traits, site fidelity, and historical high representativeness as bycatch in artisanal fisheries. This species is listed as Critically Endangered (CR), both in the IUCN and the Brazilian Red Lists. Its vulnerability is so high that its recovery potential requires protection from ongoing fishing pressure. Objective In this context, this study aimed to evaluate the health status of Daggernose sharks and their ability to cope with allostatic overload in a comparative analysis with other Carcharhinid and Sphyrnid sharks. Methods Sharks incidentally caught by the artisanal fleet in the state of Maranhão, on the Brazilian Amazon Coast, were sampled for blood, and serum was used to assess biochemical markers. Results The findings indicate significant differences in Daggernose Shark homeostatic capacity for ALP, ALT/GTP, creatinine, lactate, urea, total cholesterol, and triglycerides, pointing to lower health scores and recovery capacity when compared to other Carcharhiniformes inhabiting the same region. Discussion and conclusions It is possible that such vulnerability is a result of fisheries-induced evolution, leading to remaining populations with very low chances of fully recovering. Conservation planning is thus urgent, as current legislation based on fishing bans does very little for the species. International collaboration and longterm recovery measures are necessary, including the creation of MPAs specially designed for the species and captive maintenance aiming to monitor health status and carry out breeding attempts.